Pelatihan Spray Anti Nyamuk Berbahan Alami sebagai Solusi Ramah Lingkungan untuk Pengendalian Nyamuk Aedes aegypti - Susanto, Sharon; Christian, Yulius Evan; Wijardi , Calista; Nathali, Nathali; Susanto , Jessica Mutiara; Agustine , Grace Nathania (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) remains a public health concern, particularly in densely populated urban communities. The prolonged use of chemical-based insecticides poses health and environmental risks, necessitating the adoption of safer, natural alternatives. This community service program aimed to enhance public knowledge and skills through education and training on the formulation of mosquito repellent spray using lemongrass and lavender. The methods included interactive lectures, group discussions, and hands-on workshops. Evaluation was conducted using a pre-test and post-test consisting of 10 multiple-choice questions. Results showed a significant increase in the average score from 78.3 to 88.67. The median score improved from 80 to 90, while the minimum and maximum scores remained constant (60 and 100, respectively). These findings indicate that the practical-based learning approach effectively increased participants’ understanding of the risks of chemical insecticides and the benefits of natural repellents. Additionally, participants demonstrated high enthusiasm and interest in reproducing the herbal spray independently. This program not only improved environmental health literacy but also opened opportunities for household-scale entrepreneurship using eco-friendly products. Similar activities are recommended for replication in other areas, with further development and cross-sector collaboration.